The use of photo-elicitation in field research - Elisa Bignante (EchoGéo)
This paper examines the use of visual methods in geographical field research, and in particular photo-elicitation. The technique involves photos, videos and other forms of visual representation used in an interview, with informants asked to comment on the images. The aim is to promote more direct involvement of the informants in the research process and to encourage and stimulate the collection of quantitatively and qualitatively different information to that obtained in conventional interviews. The potential and limitations of this technique in the field are investigated, describing and discussing photo-elicitation data collection in the Maasai village of Mkuru in northern Tanzania to explore the use and preservation of natural resources. Results and methodological insights from the fieldwork are presented and discussed.